Physical and mechanical properties of rubberwood particleboard made with furfuryl alcohol added urea formaldehyde resin - Sek, Bih Fang (2019)
The objective of this study was to determine the dimensional stability properties and mechanical strength of the rubberwood particleboard made after addition of furfuryl alcohol to urea formaldehyde resin. The main issue in this research was the dimensional instability of rubberwood particleboard as wood is a hygroscopic material which loses and gains moisture as a result of changes in humidity. Chemical modification on the rubberwood particleboard such as acetylation and furfurylation are great in improving the dimensional of particleboard. In this study, the chemical treatment by applying furfuryl alcohol added UF resin was used to treat the rubberwood particleboard due to the significant performance improvement of modified woods and small environmental impact. This study proposed a procedure in which rubberwood particleboard was treated with furfuryl alcohol added UF resin followed by the condition of palm oil addition or without palm oil in the particleboard samples fabrication. Properties such as mechanical strength, dimensional stability and density of the particleboard made with treated and untreated particles were examined. The results showed that there was highly significant effect of furfuryl alcohol added UF resin treatment to water absorption, thickness swelling, MOR, MOE and IB of the rubberwood particleboard. These findings in turn support that furfuryl alcohol added UF resin treatment have greatly enhanced the dimensional stability and mechanical properties of rubberwood particleboard.